PENYULUHAN KESEHATAN DAN PENDAMPINGAN PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS MUARA RAPAK BALIKPAPAN - Shoufiah, Rahmawati; Andraini, Rus (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
Hypertension is a condition where a person experiences an increase in blood pressure above normal which can result in morbidity (morbidity) and mortality (morality). Hypertension if not controlled can cause complications such as heart disease, stroke, kidney disease, retinopathy (retinal damage), peripheral blood vessel disease, nerve disorders. The health problem that stands out in the Muara Rapak Balikpapan Community Health Center working area is that hypertension ranks first among the diseases with the highest coverage of non-communicable diseases. Over the past year, there has been an increase in hypertension sufferers by 996 people, and data for the last 4 (four) months, namely from January to April 2022, 544 cases of hypertension have been found. Health education activities in the community and assistance to hypertension sufferers which aim to increase public knowledge about the symptoms and risks as well as ways to prevent and control hypertension so as to reduce the risk of hypertension for individuals, families and those around them. This community service activity was carried out from July to November 2023 in the working area of ​​the Muara Rapak Balikpapan Community Health Center. The method of this activity is health education in the community and assistance to hypertension sufferers by providing health education and monitoring blood pressure in sufferers. The results of this community service activity include an increase in knowledge with the average knowledge of participants before education being 62,6%and after education being 87,6% with an average increase in knowledge of 25%. Apart from that, based on the results of observations of the blood pressure of hypertension sufferers, it can be seen that there has been an average decrease -average blood pressure in hypertensive sufferers